Improving the Management of Late-Life Depression in Primary Care: Barriers and Facilitators. (5th May 2011) - Sussman, Tamara; Yaffe, Mark; McCusker, Jane; Parry, David; Sewitch, Maida; Van Bussel, Lisa; Ferrer, Ilyan
Abstract : The objectives of this study were to elicit Canadian health professionals' views on the barriers to identifying and treating late-life depression in primary care settings and on the solutions felt to be most important and feasible to implement. A consensus development process was used to generate, rank, and discuss solutions. Twenty-three health professionals participated in the consensus process. Results were analysed using quantitative and qualitative methods. Participants generated 12 solutions. One solution, developing mechanisms to increase family physicians' awareness of resources, was highly ranked for importance and feasibility by most participants. Another solution, providing family physicians with direct mental health support, was highly ranked as important but not as feasible by most participants. Deliberations emphasized the importance of case specific, as needed support based on the principles of shared care. The results suggest that practitioners highly value collaborative care but question the feasibility of implementing these principles in current Canadian primary care contexts.